Determinan Kejadian Demam Berdarah Dengue di Kabupaten Minahasa Selatan Tahun 2016-2018 - Desty Komaling; Oksfriani Jufri Sumampouw; Ricky C Sondakh (Universitas Sam Ratulangi, 2020)
Background: Climate and environmental factors that are most instrumental in DBD disease are air temperature, humidity, and water availability. When Earth warming gradually increases, the effect is the acceleration of mosquito repellent. The research aims to describe the incidence of Dengue Haemorraghic Fever (DHF) in South Minahasa Regency in 2016-2018. Method: It is a correlational quantitative study using Time Series. This research was located in the South Minahasa district of North Sulawesi Province on September-October 2019 Data analyze univariatly and bivariatly. Result: The results of the research based on Spearman correlation test conducted obtained by the value p 0.959 mean that there is no significant relationship between air temperature and the incidence of DHF, Spearman correlation test conducted obtained the p-value of 0.031 is mean There is a significant link between the rainfall with the incidence of DHF, Spearman correlation test conducted obtained by the value of 0.273 This means there is no significant link between the humidity of air with the incidence of DHF, the Spearman correlation test obtained p-value of 0.776 This means there is no significant relationship between population density with the incidence of DHF. From the results of the research conducted on macro climate relations and population density with the incidence of DHF in the region of South Minahasa Regency in the year 2016-2018. Conclusion: It can be concluded there has no correlation between temperature, humidity and population density with the incidence of DHF but has correlation between the rainfall with the incidence of DHF.